Imminent myocardial infarction prediction model - Gustafsson, Stefan (SciLifeLab Serve, 2026)
Imminent myocardial infarction prediction model. In patients free from prior cardiovascular disease, we aimed to identify characteristics of an imminent first heart attack and design a prediction model.